(untitled) (Jurnal Destinasi Pariwisata, 2025)
The Museum Bali in Denpasar faces fluctuating visitor numbers and rising competition. This study aims to identify internal and external factors affecting Museum Bali’s marketing performance and to formulate strategic recommendations. A descriptive qualitative methodology was applied, collecting data through observation, interviews, documentation, and literature review. Data analysis employed the 7P marketing mix framework for internal assessment and PESTEL analysis for external evaluation, followed by SWOT integration to derive strategic alternatives. Findings reveal that Museum Bali’s authentic artefact collections and central location constitute key strengths, while limited interactive displays, infrastructural constraints, and suboptimal digital promotion represent significant weaknesses; externally, opportunities include post-pandemic tourism revival and digital technology adoption, whereas competition and budgetary limitations pose threats. Four tailored strategies are proposed: creative digital content (SO), digital service enhancement (ST), community partnerships and flexible pricing (WO), and low-cost promotional campaigns (WT). Implementing these strategies is expected to increase visitor engagement and reinforce Museum Bali’s position as a premier cultural tourism destination. It is recommended that museum management prioritize interactive digital platforms, staff training, and collaborative outreach programs.